Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a, 2012 x 24 + 77 x 2012 - 2012
= 2012 x (24 + 77 - 1)
= 2012 x 100
= 201 200
b, 33 x 76 + 84 x 27 + 32 x 3 x 40
= 27 x 76 + 84 x 27 + 27 x 40
= 27 x (76 + 84 + 40)
= 27 x 200
= 5400
a, A = \(\dfrac{3^9\times3^{20}\times2^8}{3^{24}\times243\times2^6}\)
A = \(\dfrac{3^{29}\times2^8}{3^{24}\times3^5\times2^6}\)
A = \(\dfrac{3^{39}\times3^{20}\times2^8}{3^{29}\times2^6}\)
A = 22
A = 4
b, \(\dfrac{2^{15}\times5^3\times2^6\times3^4}{8\times2^{18}\times81\times5}\)
B = \(\dfrac{2^{21}\times3^4\times5^3}{2^3\times2^{18}\times3^4\times5}\)
B = \(\dfrac{2^{21}\times3^4\times5^3}{2^{21}\times3^4\times5}\)
B = 52
B = 25
a,3+2x-1=24-[42-(22-2)]
=>3+2x-1=24-(16-2)
=>3+2x-1=24-14
=>3+2x-1=10
=>2x-1=10-3
=>2x-1=7
=>sai đề
a, 3x+2 - 8.3x = 81
<=> 3x.9 - 8.3x = 81
<=> 3x(9 - 8) = 81
<=> 3x = 81
<=> 3x = 34
<=> x = 4
b, (x - 1)2 = (x - 1)3
<=> (x - 1)2 - (x - 1)3 = 0
<=> (x - 1)2.[1 - (x - 1)] = 0
<=> (x - 1)2.(1 - x + 1) = 0
<=> (x - 1)2.(2 - x) = 0
<=> \(\left[{}\begin{matrix}\left(x-1\right)^2=0\\2-x=0\end{matrix}\right.\Leftrightarrow\left[{}\begin{matrix}x-1=0\\x=2\end{matrix}\right.\)\(\Leftrightarrow\left[{}\begin{matrix}x=1\\x=2\end{matrix}\right.\) (thỏa mãn)
@Kfkfj
a: \(\Leftrightarrow3^x\cdot9-8\cdot3^x=81\)
\(\Leftrightarrow3^x=81\)
hay x=4
b: \(\left(x-1\right)^3=\left(x-1\right)^2\)
\(\Leftrightarrow\left(x-1\right)^2\left(x-2\right)=0\)
hay \(x\in\left\{1;2\right\}\)
a) (4x - 1)2 = 25.9
=> (4x - 1)2 = 52 . 32 = 152
=> 4x - 1 = 15
=> 4x = 16
=> x = 4
b) 2x + 2x+3 = 144
=> 2x + 2x . 23 = 144
=> 2x (1 + 23) = 144
=> 2x . 9 = 144
=> 2x = 16
=> x = 4
c) đề chắc chắn đúng chứ :v
d) (2x + 1)3 - 12 = 15
=> (2x + 1)3 = 27
=> (2x + 1)3 = 33
=> 2x + 1 = 3 => 2x = 2 => x = 1
2. 2x = 16 => 2x = 24 => x = 4
3x = 81 => 3x = 34 => x = 4
x3 = 64 => x3 = 43 => x = 4
x2 =81 => x2 = 92 => x = 9
Bài 1 :
a) 5x = 125
=> 5x = 53
=> x = 3
b) 34 . 3x = 37
=> 4 + x = 7
=> x = 7 - 4
=> x = 2
a) \(3^{x-2}=3^4\)
\(x-2=4\Rightarrow x=6\)
b) \(2^x+2^{x+1}=24\)
\(2^x.\left(1+2\right)=24\)
\(2^x.3=24\)
\(2^x=\frac{24}{3}=8=2^3\Rightarrow x=3\)
a) ta có :\(3^{x-2}=81\left(=\right)3^{x-2}=3^4=>x-2=4\left(=\right)x=6\)
b) ta có :\(2^x+2^{x+1}=24\left(=\right)2^x.\left(1+2\right)=24\left(=\right)2^x.3=24\left(=\right)2^x=8\left(=\right)2^x=2^3=>x=3\)
học tốt